Mechanically robust superhydrophobic and superoleophobic coatings derived by sol–gel method. (5th January 2016) - Wu, Xinghua; Fu, Qitao; Kumar, Divya; Ho, Jeffrey Weng Chye; Kanhere, Pushkar; Zhou, Huanfu; Chen, Zhong
Abstract: Mechanically robust coatings that display both superhydrophobic and superoleophobic behavior are of great interest for a wide range of applications including sports facilities, automobile and aircraft, solar panels, and wind turbine blades. In this study, a novel method of combining both low and high surface energy SiO2 nanoparticles was employed to prepare superhydrophobic and superoleophobic coating by sol–gel method. The hydrophobicity and oleophobicity of the coatings were analyzed by various liquid droplets with surface energy ranging from 72.4 to 29.5 mJ/m 2 . Pencil scratch test, cross-cut tape adhesion test, nano-indentation, and PosiTest Pull-Off adhesion test were carried out for the coating mechanical properties. Tuning of surface topology was carried out by controlling molar ratio of low and high surface energy SiO2 nanoparticles. It is observed that with the molar ratio at 2:4 between the low and high surface energy SiO2 nanoparticles, the coating gives rise to the best superoleophobicity and mechanical properties. Such coatings hold good promise for self-cleaning and anti-icing applications under mechanically erosive/abrasive environment. Graphical abstract: Highlights: Superoleophobic and superhydrophobic coatings based on different surface energy SiO2 nanoparticles are developed by a sol–gel method. Ratio of low and high surface energy silica particles affects the coating properties. An optimum coating displays repellency to liquids of surface energy from 72.4 to 29.5 mJ/m 2 . The coating also shows good adhesion to substrate with excellent resistance to pencil scratch.